Interleukin-8 Concentration Correlation with the Size of Hydatid Cyst in Patients with Hydatidosis and Hepatitis C Mixed Infection (Case Control Study) - Eman Hasani AL-Salami; Marwa Rahman Mohamed Alsaedi; Nadia Habeeb Sarhan Sarhan Alshabanii; Saif Jabbar Yasir (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background:Hydatid cyst is a disease that is transmitted from the lactating animals that come into contactwith a person, and its danger is to generate hydatid cysts that may put pressure on some vital organs inthe human body. Here comes the role of joint infection with other pathogens such as the hepatitis C virus,especially in the same organs that are infected with the parasite, which may result from these mixed infectionsserious disease complicationsAim of study: The present study aimed to examine the possibility of a relationship between interleukin-8concentration level with the size of Hydatid cyst patients with mixed infection of hydatidosis and hepatitisC virus.Patients and Methods: The current research was run for the period January 2019 to January 2020. Thepatients were referred to AL-Furat al-awsat Hospital , Al-Sadder medical city, Public Health Laboratoryand Al-Hakeem Hospital in Al- Najaf governorate, Iraq. Eighty samples were divided into two groups. Thisfirst group was comprised of 40 patients with hydatidosis, the second group comprised of 40 patients withhydatidosis and hepatitis c virus mixed infection. The patients were aged 10 to 60 years old.Result: A higher interleukin-8 concentration was observed in patients with hydatidosis compared to thehealthy group, as the interleukin-8 concentration was (89.36) While the concentration of interleukin- 8reached in the healthy group (30 .14) ,while A high concentration of interleukin 8 is observed in combinedinfection of hydatidosis and hepatitis C virus compaer with healthy group , As the concentration of interleukin8 in the combined infection of hydatidosis and hepatitis C virus (108.73) while in the healthy group (30.14 ).Conclusion: The presence of a high level of interleukin-8 in mixed-infection patients is higher than insingle-infection patients, which may lead to exacerbation and complications of hydatidosis disease.